Diet Diversity Is Associated with Beta but not Alpha Diversity of Pika Gut Microbiota - Li, Huan; Li, Tongtong; Beasley, DeAnna E.; Heděnec, Petr; Xiao, Zhishu; Zhang, Shiheng; Li, Jiabao; Lin, Qiang; Li, Xiangzhen (Frontiers in Microbiology, 2016)
Wild mammals often consume different food sources as they become geographical available. This change in diet composition is likely to influence the gut microbial community, yet it remains unclear what the relationship looks like—particularly in small herbivores–under natural conditions. We used DNA sequencing approaches to characterize the diet composition and gut microbial community of wild plateau pikas (Ochotona curzoniae) collected from three altitudes. We tested if diet and gut microbiota composition changes across altitudes, and the relationship between diet diversity and gut microbiota diversity. Our results showed that altitude significantly influences the composition of diet and gut microbial communities. Notably, the alpha diversity (Shannon diversity and observed OTUs) of individual diet was not significantly correlated with that of gut microbiota, whereas the beta diversity (Jaccard and Bray-Curtis dissimilarity) of diet was positively correlated with that of gut microbiota. Our study is the first time to highlight the relationship between diet and gut microbiota composition in wild pikas on the Qinghai-Tibet Plateau. It suggests that the species richness within individual gut microbiota does not linearly increase with diet diversity, whereas those individuals that are more similar in diet composition harbor more similar gut microbiota.